The Influence of Service Quality on Patient Loyalty Through Patient Satisfaction at Beriman Hospital, Balikpapan City - Nurfitriani, Nurfitriani (Journal of Engineering Science and Technology Management, 2024)
Customer loyalty is a key factor in a company’s success and profitability, driven by satisfaction and trust. Service quality is essential in achieving patient satisfaction, which in turn fosters loyalty. This study examines the effect of service quality on patient loyalty through satisfaction at Faith Hospital in Balikpapan City. Using a quantitative cross-sectional design, the research involved 378 outpatient respondents. The findings reveal a direct positive effect of service quality on patient satisfaction, indicating that improved service enhances satisfaction. Similarly, service quality directly influences patient loyalty, meaning better services encourage repeat visits. Patient satisfaction also directly impacts loyalty, showing that higher satisfaction strengthens loyalty. Additionally, an indirect effect exists, where service quality boosts loyalty by increasing satisfaction. The study recommends that hospital management maintain and enhance service quality to improve patient satisfaction and loyalty. Specific improvements include optimizing waiting room comfort, maintaining cleanliness, expanding parking areas, and reducing service wait times. Creating a positive first impression during visits is also crucial for long-term patient commitment. These measures can strengthen loyalty, ensuring patients continue choosing the hospital for future healthcare needs. By prioritizing service quality and patient satisfaction, Faith Hospital can foster lasting loyalty, supporting its long-term success and profitability.